Toraja Cultural Immersion: A Community Service Initiative for a Higher Education in Australia - Markus Deli Girik Allo; Roni La'biran; Judith Ratu Tandiarrang; Elim Trika Sudarsi; Nilma Taula'bi; Venni Banne Tasik (STAI Hubbulwathan Duri, 2024)
Cultural immersion programs are increasingly recognized for their role in fostering cross-cultural exchange, deepening cultural understanding, and promoting mutual learning. This study investigates the impact of a Toraja Cultural Immersion program, held in Bali from 6–21 July 2024, involving students from the University of Western Australia (UWA) and the English Education Study Program at UKI Toraja. A qualitative research design was adopted to evaluate the program's outcomes for participants and the host community. Twenty-one UWA students and seven UKI Toraja members were selected through purposive sampling to ensure diverse perspectives. Data were collected via semi-structured interviews and participant observation during activities such as teaching, cultural rituals, and community service. Thematic analysis was applied to transcribed data to identify recurring themes. The findings reveal that the program significantly enhanced participants' cultural awareness and intercultural competence. UWA students gained deeper insights into Toraja culture and demonstrated improved adaptability and understanding of cultural nuances. Meanwhile, members of UKI Toraja observed increased enthusiasm for English language learning and cultural preservation efforts within their community. The program successfully bridged cultural gaps, fostering mutual learning and providing educational benefits for both groups. The involvement of local facilitators from UKI Toraja was pivotal in contextualizing cultural experiences and guiding participants. This study underscores the value of cultural immersion programs in promoting intercultural competence and educational exchange. Future research should explore the long-term effects of such programs on participants' personal and professional development.